To the Top of the Mountain - Dahl, Arne, 1963-; Translated from the Swedish by Menzies, Alice (London Harvill Secker, 2014)
"In the third installment in Arne Dahl's award-winning Intercrime series, a unit of seven elite detectives is reunited when their individual cases turn out to have deadly connections. A VINTAGE CRIME/BLACK LIZARD ORIGINAL. Stockholm's Intercrime team--a specialized group created to investigate violent, international crime--was split up after their last case ended disastrously. Their leader has been forced into early retirement, and his six officers have been reassigned. Detectives Paul Hjelm and Kerstin Holm are investigating the senseless murder of a young soccer supporter in a pub in Stockholm, Arto Stockholm, Arto Söderstedt and Viggo Norlander are dispatched to mundane cases around the city, Gunnar Nyberg is on the child abuse team, and Jorge Chavez is immersed in dull research tasks. But when an inmate is blown up in a high-security prison, a drug baron comes under attack, and a massacre takes place in a dark suburb, the Intercrime team is urgently reconvened. There is something dangerous approaching Sweden, and it's believed they are the only people who can do anything to stop it"
Keywords: Detective and mystery stories -- Police -- Sweden--Stockholm